2014
DOI: 10.1111/1471-0528.12836
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of robot‐assisted hysterectomy: a cost‐minimisation analysis

Abstract: Objective The aim of this study was to carry out an economic evaluation of robot-assisted hysterectomy compared with the current standard of care in Ireland.Design Cost-minimisation analysis of robot-assisted hysterectomy compared with a combination of traditional open and conventional laparoscopic surgery.Setting The publicly funded healthcare system in Ireland.Population The target population was women requiring hysterectomy that could be completed using robot-assisted surgery.Methods A simulation-based econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 20 publications
4
47
0
Order By: Relevance
“…Of these, full economic evaluation (i.e. cost-effectiveness, cost-minimisation, cost-utility, cost-benefit analysis) was performed in only six (13 %) [11][12][13][14][15][16]; the remaining articles reported cost analysis. Of note is that in many of these studies effectiveness data were also reported in the same article but these data were not interpreted along with the cost data as they would be in a full economic evaluation.…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, full economic evaluation (i.e. cost-effectiveness, cost-minimisation, cost-utility, cost-benefit analysis) was performed in only six (13 %) [11][12][13][14][15][16]; the remaining articles reported cost analysis. Of note is that in many of these studies effectiveness data were also reported in the same article but these data were not interpreted along with the cost data as they would be in a full economic evaluation.…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the 47 studies, 34 (72 %) were conducted in USA , two each in Switzerland (4 %) [51,52], Canada (4 %) [15,53], Ireland (4 %) [14,16] and Australia (4 %) [13,54], and one each in Denmark (2 %) [12], Italy (2 %) [55], Spain (2 %) [56], Sweden (2 %) [57] and the UK (2 %) [11].…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The target population was clearly stated as women requiring hysterectomy that could be completed using robot-assisted surgery. Vaginal hysterectomies were therefore excluded from the analysis.…”
Section: Authors' Replymentioning
confidence: 99%